Best Relay Selection Scheme in Wireless Cooperative Communication - Hidayati, Nurul; Kusumawardani, Mila; Mas’udia, Putri Elfa (Jurnal Jaringan Telekomunikasi, 2023)
In this research, the combination of the relay selection and network coding is used to measure the performance in LOS and NLOS condition over cooperative communication. The research aims are to select the best relay as assisted relay as well as to improve performance system. The research method used four nodes, two nodes as source and destination and two nodes as relays. The single relay selection is used to select best relay of several relays. Measurements are conducted by altering the positions of the relays to achieve optimal outcomes. The findings indicate that the relay with the lowest Bit Error Rate (BER) and the shortest distance is chosen. The study's outcomes, when measuring throughput, reveal that network coding throughput is 21.8% higher than that without network coding in Non-Line of Sight (NLOS) conditions. In Line of Sight (LOS) conditions, the throughput is increased by 23%.